Comprehensive Analysis of N6-Methyladenosine Regulatory Genes from Citrus grandis and Expression Profilings in the Fruits of “Huajuhong” (C. grandis “Tomentosa”) during Various Development Stages - Yuzhen Tian; Jiwu Zeng; Ruiyi Fan (Horticulturae, 2022)
Citrus grandis “Tomentosa” (“Huajuhong”) is a famous traditional Chinese medicine. The aim of the present study is to provide a comprehensive characterization of the m6A regulatory genes from C. grandis, and examine their expression patterns in fruits of C. grandis “Tomentosa” during various developmental stages. A total of 26 N6-methyladenosine (m6A) regulatory proteins were identified from the genome of C. grandis, which were distributed across nine chromosomes in C. grandis. Phylogenetic relationships revealed that all m6A regulatory genes were divided into groups of m6A writers, erasers, and readers. The m6A writer groups included CgMTA, CgMTB, and CgMTC three MTs (methyltransferases), one CgVIR (virilizer), one CgHAKAI (E3 ubiquitin ligase HAKAI), and one CgFIP37 (FKBP interacting protein 37). Moreover, 10 CgALKBH (α-ketoglutarate-dependent dioxygenase homolog) members (numbered from CgALKBH1 to CgALKBH10) and 10 CgECT (C-terminal region) members (numbered from CgECT1 to CgECT10) in C. grandis were identified as m6A erasers and readers, respectively. The domain structures and motif architectures among the groups of m6A writers, erasers, and readers were diverse. Cis-acting elements in the promoters of the 26 m6A regulatory genes predicted that the abscisic acid-responsive (ABA) element (ABRE) was present on the promoters of 19 genes. In addition, the expression profiles of all m6A regulatory genes were examined in the fruits of two varieties of C. grandis “Tomentosa” during different growth stages to give basic hints for further investigation of the function of the N6-methyladenosine regulatory genes in C. grandis “Tomentosa”.